Endobronchial mucormycosis successfully treated with pharmacologic therapy: A rare case report - Soo Kyun Jung; Keum-Ju Choi (Respiratory Medicine Case Reports, 2025)
A 36-year-old female patient who did not have a previous history of any disease visited our institution because of shortness of breath. The patient was first diagnosed with diabetes upon admission. Chest computed tomography (CT) scan showed a lesion that completely obstructed the left main bronchus and pneumonia. Due to hypoxia, the patient was placed on mechanical ventilation and admitted to the intensive care unit. Bronchoscopy was performed, and results revealed complete atelectasis with a soft tissue mass at the left main bronchus. Bronchoscopic biopsy confirmed that the patient's condition was endobronchial mucormycosis. Treatment with liposomal amphotericin B was started. After 1 week, atelectasis improved based on the chest radiography result. The patient was successfully extubated. However, 4 weeks after treatment, bronchoscopy still showed complete atelectasis with purulent secretion and a soft tissue mass. After 6 weeks, liposomal amphotericin B was switched to isavuconazole, with a duration of 2 months. After completing the treatment, bronchoscopy showed no endobronchial lesion. Herein, we present a rare case of rapidly progressing endobronchial mucormycosis in a young patient who did not have a previous history of any disease and who was successfully managed with pharmacological therapy.